Biological characterization of the Amazon coral Micrurus spixii snake venom: isolation of a new neurotoxic phospholipase A2 - Terra, Angelo Laurence Covatti [UNESP]; Moreira-Dill, Leandro Soares; Simões-Silva, Rodrigo; Monteiro, José Roniele do Nascimento; Cavalcante, Walter Luís Garrido [UNESP]; Gallacci, Márcia [UNESP]; Barros, Neuza Biguinati; Nicolete, Roberto; Teles, Carolina Bioni Garcia; Medeiros, Patrícia Soares Maria de; Zanchi, Fernando Berton; Zuliani, Juliana Pavan; et al. (Elsevier B. V., 2015)
The Micrurus genus is the American representative of Elapidae family. Micrurus spixii is endemic of South America and northern states of Brazil. Elapidic venoms contain neurotoxins that promote curare-mimetic neuromuscular blockage. In this study, biochemical and functional characterizations of M. spixii crude venom were performed and a new neurotoxic phospholipase A2 called MsPLA2-I was isolated. M. spixii crude venom caused severe swelling in the legs of tested mice and significant release of creatine kinase (CK) showing its myotoxic activity. Leishmanicidal activity against Leishmania amazonensis (IC50 1.24 μg/mL) was also observed, along with antiplasmodial activity against Plasmodium falciparum, which are unprecedented for Micrurus venoms. MsPLA2-I with a Mr 12,809.4 Da was isolated from the crude venom of M. spixii. The N-terminal sequencing of a fragment of 60 amino acids showed 80% similarity with another PLA2 from Micrurus altirostris. This toxin and the crude venom showed phospholipase activity. In a mouse phrenic nerve-diaphragm preparation, M. spixii venom and MsPLA2-I induced the blockage of both direct and indirect twitches. While the venom presented a pronounced myotoxic activity, MsPLA2-I expressed a summation of neurotoxic activity. The results of this study make M. spixii crude venom promising compounds in the exploration of molecules with microbicidal potential.
Keywords: Microbicidal potential; Micrurus spixii; Neurotoxicity; Phospholipase a(2); Snake venom